Analisis Penentuan Harga Pokok Produksi dan Harga Pokok Penjualan pada Usahatani Jagung di Desa Owalanga Kecamatan Bongomeme - Santi Harun; Tri Handayani Amaliah; Victorson Taruh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out how the analysis determines the cost of production and cost of goods sold in Owalanga Village, Bongomeme District. This research uses a qualitative approach with descriptive methods. The sample in this study was 30 people. Data collection uses observation, interviews and documentation. Data analysis techniques use reduction, data presentation, and conclusion verification. The results of this research show that corn production is one of the main commodities that makes a significant contribution to the local economy. Based on the research results, there are several factors that influence the cost of production. (1) The majority of farmers in Owalanga Village, Bongomeme District use the NK 212 seed type. (2) The basic production costs of corn farming in Owalanga Village, Bongomeme District consist of variable costs and labor wage costs. The biggest variable cost is the purchase of NK 212 corn seeds for Rp. 600,000 per bag, and for one planting season with a land area of ​​1 hectare, 4 bags of seeds are needed. Thus, the total cost required for corn seeds in one hectare of planting season is IDR 2,400,000. (3) Labor costs in corn farming refer to the total expenditure incurred by farmers to pay salaries or rewards to workers involved in corn farming activities. These costs involve compensation for various types of work, including planting, maintaining, and harvesting corn crops. The largest cost for labor wages in corn production in Owalanga Village is land clearing costs of IDR 900,000 for 3 workers with a planting area of ​​1 ha.